Methocinnamox Produces Long-Lasting Antagonism of the Behavioral Effects of µ-Opioid Receptor Agonists but Not Prolonged Precipitated Withdrawal in Rats - Gerak, Lisa R. (J Pharmacol Exp Ther, 2019)
A novel µ-opioid receptor antagonist, methocinnamox (MCAM), attenuates some abuse-related and toxic effects of opioids. This study further characterized the pharmacology of MCAM in separate groups of rats using procedures to examine antinociception, gastrointestinal motility, and withdrawal in morphine-dependent rats. Antinociceptive effects of opioid receptor agonists were measured before and after MCAM (1–10 mg/kg) using warm water tail withdrawal and sensitivity to mechanical stimulation in inflamed paws (complete Freund’s adjuvant). Before MCAM, morphine, fentanyl, and the κ-opioid receptor agonist spiradoline dose dependently increased tail-withdrawal latency from 50°C water; MCAM attenuated the antinociceptive effects of morphine and fentanyl, but not spiradoline. Morphine increased sensitivity to mechanical stimulation and decreased gastrointestinal motility, and MCAM blocked both effects. These antagonist effects of 10 mg/kg MCAM were persistent, lasting for 2 weeks or longer. Withdrawal emerged after discontinuation of morphine treatment or administration of 10 mg/kg MCAM or 17.8 mg/kg naloxone; other than the day of antagonist administration when withdrawal signs were greater in rats that received antagonist compared with rats that received vehicle, there was no difference among groups in directly observable withdrawal signs or decreased body weight. These results confirm that MCAM is a selective µ-opioid receptor antagonist with an exceptionally long duration of action, likely due to pseudoirreversible binding. Despite its sustained antagonist effects, the duration of withdrawal precipitated by MCAM is not different from that precipitated by naloxone, suggesting that the long duration of antagonism provided by MCAM could be particularly effective for treating opioid abuse and overdose. SIGNIFICANCE STATEMENT: The opioid receptor antagonist MCAM attenuates some abuse-related and toxic effects of opioids. This study demonstrates that MCAM selectively antagonizes multiple effects mediated by µ-opioid receptor agonists for 2 weeks or longer, and like naloxone, MCAM precipitates withdrawal in morphine-dependent rats. Despite this persistent antagonism, withdrawal signs precipitated by MCAM are not significantly different from signs precipitated by naloxone or occurring after discontinuation of morphine, suggesting that using MCAM for opioid abuse or overdose would not produce sustained withdrawal.